1990
DOI: 10.1139/p90-189
|View full text |Cite
|
Sign up to set email alerts
|

Low-lying states in 97Mo and 101Mo by (t, d) and (d, p) reactions on the neighbouring molybdenum isotopes

Abstract: The values of spins, parities, and spectroscopic factors for neutron transfer have been determined for many low-lying states in 97Mo and 101Mo by a study of the (t, d) and (d, p) reactions on the neighbouring even-mass isotopes. Eighteen new values of Jπ have been obtained for these nuclei. Values of the fullness and emptiness parameters V2 and U2 have been suggested for the 3s1/2 and 2d5/2 orbitals in 100Mo. (Nuclear structure 97Mo, 101Mo, measured J,π, and spectroscopic factors for states up to ~2.0 MeV usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…With the purpose of studying the nuclear structure of Mo isotopes such as 101 Mo, Hjorth et al have also reported the irradiation of Mo targets with 15 MeV deuterons 89 . Habib et al performed irradiations of 100 Mo with both a 12 MeV deuteron and a 14 MeV triton beam in order to target the 100 Mo( d , p ) 101 Mo and 100 Mo( t , d ) 101 Mo reactions, respectively, with the intention of studying the nuclear structure and spectroscopic states of 101 Mo 90 .…”
Section: Productionmentioning
confidence: 99%
“…With the purpose of studying the nuclear structure of Mo isotopes such as 101 Mo, Hjorth et al have also reported the irradiation of Mo targets with 15 MeV deuterons 89 . Habib et al performed irradiations of 100 Mo with both a 12 MeV deuteron and a 14 MeV triton beam in order to target the 100 Mo( d , p ) 101 Mo and 100 Mo( t , d ) 101 Mo reactions, respectively, with the intention of studying the nuclear structure and spectroscopic states of 101 Mo 90 .…”
Section: Productionmentioning
confidence: 99%
“…Molybdenum isotopes have been studied in neutron transfer experiments. There are several published studies of the (d, p) and (p, d) reactions on 100 Mo [22][23][24][25][26][27][28][29][30][31]. Studies of both these reactions, albeit fewer in number, have been made on targets of 98 Mo [27,[32][33][34] and 102 Ru [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%